2018
DOI: 10.1177/1758834017751635
|View full text |Cite
|
Sign up to set email alerts
|

The constitutively active PKG II mutant effectively inhibits gastric cancer development via a blockade of EGF/EGFR-associated signalling cascades

Abstract: Type II cyclic guanosine monophosphate (cGMP)-dependent protein kinase (PKG II) is a membrane-anchored enzyme expressed mainly in the intestinal mucosa and the brain, and is associated with various physiological or pathological processes. Upregulation of PKG II is known to induce apoptosis and inhibit proliferation and metastasis of cancer cells. The inhibitory effect of PKG II has been shown to be dependent on the inhibition of the activation of epidermal growth factor receptor (EGFR) and blockade of EGFR dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Our results also confirmed that l -Arg-triggered PKG II activation blocked Raf/MEK and PI3K/Akt signaling pathways. Furthermore, the activated PKG II could also inhibit the upstream protein EGFR activation which is consistent with previous results [37]. All these data further confirm the inhibitory effect of activated PKG II on OC cells, indicating that PKG II maybe an anti-cancer factor with extensive effects.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also confirmed that l -Arg-triggered PKG II activation blocked Raf/MEK and PI3K/Akt signaling pathways. Furthermore, the activated PKG II could also inhibit the upstream protein EGFR activation which is consistent with previous results [37]. All these data further confirm the inhibitory effect of activated PKG II on OC cells, indicating that PKG II maybe an anti-cancer factor with extensive effects.…”
Section: Discussionsupporting
confidence: 92%
“…Most of these DEmRNAs are closely associated with carcinogenesis and progression, for example CCND1, 61 VIM, 62 and EGF. 63 Specifically, CCND1 and EGF were identified as the main genes, and enriched in multiple pathways associated with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, upregulation of EGFR leads to poor survival through the activation of angiogenesis in glioblastoma ( 25 ). Effective inhibition of EGFR activation was indicated to ameliorate gastric tumor development through a delay in growth, induction of apoptosis, as well as inhibition of metastasis and angiogenesis ( 26 ). PAK1 is the best-characterized member of an evolutionarily conserved family of serine/threonine kinases, which has a key role in the regulation of cell morphogenesis, motility, mitosis and angiogenesis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%